The Embedding Performance of StegSVM Model in Image Steganography - Hanizan Shaker Hussain; Roshidi Din; Mohd Hanif Ali; Nor Balqis (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper focuses on one of the areas of information hiding which is image steganography. It proposes the StegSVM model as an embedding technique in steganography that has exploited human visual system through Shifted LSB that shows an expected performance. The performance of this technique evaluation is based on imperceptibility and robustness of the technique compared to the other previous models in image steganography doamin. Thus, the result shows that the proposed StegSVM model is promising. For further work, it is suggested that the other image domain through other intelligent methods should be investigated.